Carbon Origami via an Alumina-Assisted Cyclodehydrofluorination Strategy - Steiner, Ann-Kristin; Sharapa, Dmitry; Troyanov, Sergey; Nuss, Jurgen; Amsharov, Konstantin (Chemistry - A European Journal, 2021)
Rational folding of nanographenes has the potential to penetrate the barrier between macro- and micro-worlds for the engineering of carbon-based materials with functional molecular shapes. This work reports that an alumina-mediated C-F bond activation strategy is able to tackle this challenge allowing both the effective incorporation of non-hexagonal rings and the formation of helical structures leading to the folding of nanographenes akin to origami. More information can be found in the Full Paper by K. Amsharov et al. (DOI: 10.1002/chem.202003448).
CRIS-Team WoS Importer:2021-04-09